Gender-Based Violence in Sexual Minority Relationships: Cognitive Thresholds and Support Systems - Xinhao Wan (Lecture Notes in Education Psychology and Public Media, 2026)
Gender-based violence (GBV) in sexual minority relationships remains underexplored because dominant cultural scripts still frame abuse through a heterosexual male-female lens. This paper analyzes the cognitive logic that shapes how such violence is recognized, tolerated, or ignored across two socio-cultural settings. Drawing on minority stress theory, the power and control model, and heteronormativity, the study adopts a qualitative comparative approach based on discourse analysis of legal texts, media narratives, and secondary data from community support organizations. It compares Region A, a socially liberal urban context with visible legal protections, and Region B, a conservative setting where traditional family values and institutional silence shape sexual minority life. The analysis shows that the definition of violence is culturally contingent. Verbal humiliation, coercive concealment, and forced outing operate as powerful tactics of control, but their social legibility differs significantly across regions. Region B raises the threshold for help-seeking through stigma and legal silence, whereas Region A benefits from stronger informal support and media representation. The paper argues for culture-sensitive support systems that recognize identity-based abuse and make invisible victims more visible.